Modeling the Human Development Index Seen from the Aspect of Public Health in East Java - Annisaa, Annisaa; Rochmah, Siti Nur; Alma, Lucky Radita (Populasi, 2023)
The country should invest in health development to raise the standard of its human resources. The human development index (HDI) of a state can be impacted by health development as determined by the public health development index. Finding a prediction model for HDI in terms of public health development indicators was the aim of this study. The method used here is that for each district and city in East Java Province in 2018, secondary data on HDI and public health development indicators were collected. The Statistics Indonesia and the Health Research and Development Agency provided secondary data. Multiple linear regression analysis was performed on the data using the SPSS 26 program. Results show that the variables of toddler health, reproductive health, health services, health behavior, non-communicable diseases, and environmental health are significantly related to HDI, while the prediction for HDI based on linear regression model of this study is HDI = 44.831 + 20.347* indicators of health service indicators + 42.511* indicators of health behavior – 12.208* indicators of non-communicable diseases. Based on this model, it is necessary to pay more attention to health services, health behavior, and trends in non-communicable diseases in the community in order to increase the HDI rate in East Java Province.